The Negative Externality of Mining Activities in Brown Canyon - Aini Furoida; Indah Susilowati (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2021)
The negative impact of mining activites has resulted in environmental damage that reduces environmental functions. One of them is the brown cnyoan mining, whose mining operations have resulted in the loss of of clean water sources and disrupted public health. The research aims to analyse the negative externalities received bt the community and to estimate the economic losses of the community due to mining activites. The data source of this research is primart data with a sample of 50 families using the purposive sampling method. This research uses a mixed-method, which is a combination of qualitative data (indepth interview, descriptive and coding criteria) and quantitative data (resplacement cost and cost od illness). This research shows that the dominant-negative externalities felt by the community are mining nose, decrease water quality and air pollution. The estimated loss from the replacement cost approach is 5,662,500 IDR and the cost of illness approach 3,999,000 IDR, with an average loss per family each month od 192,030 IDR. This negative impact mining disrupts community efficiency because the negative impact is not taken into account by producers in determining mining production.